Schizophrenia in the Specialized Pharmaceutical Component: Clinical and Pharmacoepidemiological Aspects (Research, Society and Development, 2020)
Schizophrenia is part of a group of serious mental disorders, which has no characteristic symptoms. The drug treatment of this disease consists of the use of first generation (typical) antipsychotics, contemplated in primary care, and the second generation (atypical), which are included in the Specialized Component of Pharmaceutical Assistance (CEAF). The study aims to analyze the clinical and pharmacoepidemiological aspects of patients with schizophrenia assisted by CEAF in Teresina, Piauí. This is a descriptive, observational, cross-sectional study with a quantitative approach on the topic. Researches that report the clinical aspects related to serious mental disorders become a reference in the subject, provide epidemiological data about the disease and are useful for directing the implementation of health services for these patients., The data were collected through interviews using a questionnaire. Regarding the first symptoms presented by the patients, the most frequent were hallucinations and aggression, men suffer more from the disorder, the drug Olanzapine is the most dispensed, followed by Quetiapine. Hallucination is generally the first sign presented by the patient, conventional treatments using antipsychotic drugs are effective, but subject to serious adverse effects. Thus, patients who have this disease have impaired social life, requiring continuous care, use of drugs to control the disease, and the monitoring of the pharmaceutical professional, which is crucial to optimize pharmacotherapy, aiming at a better quality of life.